1998
DOI: 10.1063/1.366614
|View full text |Cite
|
Sign up to set email alerts
|

Texture control of PbTiO3 and Pb(Zr,Ti)O3 thin films with TiO2 seeding

Abstract: The nature and the role of 1 to 5 nm thick TiO 2 seed layers for the growth of textured PbTiO 3 and Pb(Zr,Ti)O 3 thin films on textured Pt(111) thin film substrates have been studied. Under otherwise identical in situ sputter deposition process conditions, the PbTiO 3 texture could be turned from (100) to (111) orientation by adding the seed layer. This is demonstrated by patterning the TiO 2 film. Auger electron spectroscopy and x-ray photoemission spectroscopy showed that the seed layer was a continuous TiO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
135
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(146 citation statements)
references
References 29 publications
10
135
1
Order By: Relevance
“…This fact was also observed in case of other thin film Ti-oxide compounds grown by pulsed Laser deposition (PLD) [57]. The rutile phase was also found by Muralt et al for sputtered PZT films [58].…”
Section: Titanium Ti L 23 Absorption and Emission Spectrasupporting
confidence: 55%
“…This fact was also observed in case of other thin film Ti-oxide compounds grown by pulsed Laser deposition (PLD) [57]. The rutile phase was also found by Muralt et al for sputtered PZT films [58].…”
Section: Titanium Ti L 23 Absorption and Emission Spectrasupporting
confidence: 55%
“…To induce other preferential orientations the use of seeding layers or the change of the substrate choice is necessary. Among these methods, the introduction of an additional layer of TiO x , on which we grow the PZT films, results in a 111 preferential orientation [10,11]. The same TiO x layer plays a major role in the epitaxial growth of (001) PZT films on Pt(100)/MgO(100) [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it has been suggested that either a Pt-Ti intermetallic or TiO 2 on the Pt surface provide a templating layer for (111) epitaxial perovskite growth [14,17].…”
mentioning
confidence: 99%
“…If no Ti layer was present, the SrTiO 3 thin films were predominantly (110) oriented, although they also showed an epitaxial relationship with the (111) Pt electrode [12]. Ti adhesion or surface layers have also been shown to promote epitaxial growth on (111) Pt grains for other perovskite films [14][15][16][17].…”
mentioning
confidence: 99%